Probable micronutrient deficiency diseases in a rural community. The nonadults of Mary's Nativity church, 16th century, Trentino Alto-Adige, Italy. (February 2023) - Larentis, Omar; Licata, Marta; Tonina, Enrica; Pangrazzi, Caterina
Highlights: Forty-one child skeletons from early modern north Italy were analysed. Evidence of probable micronutrient deficiency disease was found. Differential diagnosis supports cases of vitamin C and D deficiency, even if other pathologies and their co-occurrence cannot be ruled out. The sample comes from a rural area and is chronologically framed in a time span of about 100 years. This study presents one of the first extensive paleopathological analyses of an Italian cemetery dedicated to children. Abstract: We discuss, with a biocultural perspective, the connection between living condition related to the Great Peasants' Revolt and health status of the nonadult population from the 16th century North-eastern Italy, with a particular focus on those caused by micronutrients C and D. We analysed forty-one skeletons of nonadults in primary deposition with macroscopic examination coupled with a literature review aimed at providing a differential diagnosis. Eleven nonadults present probable cases of rickets, twelve show evidence that seems to be related to scurvy, while ten individuals feature a pattern consistent with a co-occurrence condition. Finally, eight subjects have no pathological changes or evidence, and that may be considered strictly related to C or D deficiency. This study provides a significant example of pathological lesion on nonadults coming from the same area and framed in a limited chronological period. In addition, the sample is distinguished by the number of subjects and the good preservation of their bone tissue. Finally, the work is of primary importance as the Italian panorama lacks exhaustive paleopathological publications.